1995
DOI: 10.1007/bf00790660
|View full text |Cite
|
Sign up to set email alerts
|

Movement of bromide as a tracer for nitrate in an Alfisol of the Indian Semi-Arid Tropics under rainfed condition

Abstract: The variable responses of crops to added nitrogen (N) in Alfisols of the Indian semi-arid tropics are partly due to variable rainfall and partly due to variable losses of available-N. To measure the losses of N through leaching, which can be appreciable under some circumstances, a field experiment was conducted during the rainy season (June-September) of 1992, using bromide (Br) as a tracer for NO 3. Bromide (as NaBr) was applied to bare fallow soil at a rate of 200 kg ha-I in microplots (2 m × 2 m) and its ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Irrigation experiments using a non-reactive tracer (tracer experiments) such as bromide (Br − ) provide a means of describing flow regimes in structured soils at the profile scale (Caron et al 1996; Yang & Wendroth 2014). Due to the anionic character of NO 3 − , its movement in soils is often compared with other anions, such as Br − (Smith & Davis 1974; Silvertooth et al 1992; Patra & Rego 1996), even if Br − is leached faster than NO 3 − (Clay et al 2004). Bromide, as NO 3 − , is conservative, but has the advantage of neither degrading nor volatilizing over time and thus is not lost from the soil profile other than through deep leaching and plant uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Irrigation experiments using a non-reactive tracer (tracer experiments) such as bromide (Br − ) provide a means of describing flow regimes in structured soils at the profile scale (Caron et al 1996; Yang & Wendroth 2014). Due to the anionic character of NO 3 − , its movement in soils is often compared with other anions, such as Br − (Smith & Davis 1974; Silvertooth et al 1992; Patra & Rego 1996), even if Br − is leached faster than NO 3 − (Clay et al 2004). Bromide, as NO 3 − , is conservative, but has the advantage of neither degrading nor volatilizing over time and thus is not lost from the soil profile other than through deep leaching and plant uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Bromide is routinely used as a tracer for mobile anionic plant nutrient movement (e.g., nitrate, chloride) in the soil (Fisher and Healy, 2008;Green et al, 2005;Izadi et al, 1993;Logsdon, 2007;Schuh et al, 1997;Seo et al, 2005) as well as in studies looking for offtarget movement affecting groundwater in delicate ecosystems (Elc xi and Molz, 2009;Woodward et al, 2009). In addition, it has successfully been used as a tracer of nitrogen (N) movement in both soils and plants (McLeod et al, 1998;Patra and Rego, 1995). Although most of the work using Br as a tracer in agricultural systems has focused on annual crops such as corn, wheat, potato, and cotton (Izadi et al, 1993;Kessavalou et al, 1996;Ottman and Pope, 2000;Silvertooth et al, 1992), work in the perennial forage crops (Blumenthal et al, 1999;Magarian et al, 1998;Schnabel et al, 1995) and in the citrus trees (Harrison et al, 1999) have shown Br to be a valid tracer of movement in many soil and plant systems.…”
mentioning
confidence: 99%